2022
DOI: 10.1186/s13567-022-01063-8
|View full text |Cite
|
Sign up to set email alerts
|

Bartha-K61 vaccine protects nursery pigs against challenge with novel european and asian strains of suid herpesvirus 1

Abstract: The present study investigates the pathogenicity of two recently isolated strains of Suid herpesvirus 1 (SuHV1), the Greek strain Hercules and the Chinese strain HeN1, in unvaccinated pigs and in pigs vaccinated with a Bartha-K61 strain. In an experiment performed in negative pressure kiosks (isolators), 45-day old seronegative pigs previously oronasally /intramuscularly vaccinated with the Bartha-K61 vaccine strain, along with unvaccinated controls, were challenged either with the Hercules strain or the HeN1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…A commercial kit (Bac-to-Bac, Thermo) was used to produce the recombinant baculovirus strains Ac-gB-DCpep and Ac-PorB using instructions provided by the manufacturer. Sf9 cells in logarithmic growth phase were infected with Ac-gB-DCpep and Ac-PorB at MOI = 1.0 and cultured at 27 °C for 60 h. Proteins were extracted from the culture supernatants as previously described and analyzed using Western blotting [ 9 ]. In brief, protein samples were separated using 12% sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and then electro-transferred to a polyvinylidene fluoride membrane and incubated in Tris and Tween 20 (TBS-T) containing 1:5000 dilution of anti-His monoclonal antibody (Proteintech, 66005-1-Ig, USA) for 2 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A commercial kit (Bac-to-Bac, Thermo) was used to produce the recombinant baculovirus strains Ac-gB-DCpep and Ac-PorB using instructions provided by the manufacturer. Sf9 cells in logarithmic growth phase were infected with Ac-gB-DCpep and Ac-PorB at MOI = 1.0 and cultured at 27 °C for 60 h. Proteins were extracted from the culture supernatants as previously described and analyzed using Western blotting [ 9 ]. In brief, protein samples were separated using 12% sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and then electro-transferred to a polyvinylidene fluoride membrane and incubated in Tris and Tween 20 (TBS-T) containing 1:5000 dilution of anti-His monoclonal antibody (Proteintech, 66005-1-Ig, USA) for 2 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…PR control in China had been relatively stable until the emergence of PRV variant strains in 2011 where infections occurred in pigs even though the animals had been immunized with the Bartha-K61 strain [ 5 , 6 ]. The Bartha-K61 vaccine appeared to provide only suboptimal protection against these variants [ 7 , 8 ], although other studies do show adequate protection against such variants by the Bartha-K61 vaccine strain [ 9 , 10 ]. Irrespective, the generation of vaccines that antigenically more closely match emerging variant PRV strains may represent an added value to control these infections.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, both the licensed vaccines based on classical and variant PRV strains had been used to control PR in China [ 33 ], but there was some debate about whether Bartha-K61 could protect pigs against the Chinese variant PRV strains in a past study [ 34 ]. On the one hand, some research showed that despite differences in virulence, a suitable vaccination scheme with the Bartha-K61 strain could protect pigs against variant PRV challenge by XJ5, HeN1, or Hercules [ 35 , 36 ]. On the other hand, some studies showed that Bartha-K61 was unable to provide complete protection against challenge by the variants, TJ, ZJ01, SMX, or JS-2012 [ 20 , 23 , 27 , 37 ], but the vaccine failure mechanism was not clear.…”
Section: Introductionmentioning
confidence: 99%